Bibliography on Cold Regions Science and Technology. Volume XXVIII, Part 1. - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER N H (1974)
The present volume contains material accessioned between July 1973 and June 1974. The volume consists of two parts, each separately bound. Pt. 1 contains the full citation of 4312 items, in many cases with abstracts. See also Volume 27, Part 2, AD-768 100 and Volume 28, Part 2, AD/A-007 105.